Who Will Monitor the Monitors? Informal Law Enforcement and Collusion at Champagne - GUHA, Brishti (Institutional Knowledge at Singapore Management University, 2012)
Informal monitors can sometimes substitute for formal law enforcement. Monitors hired to minimize cheating, however, are themselves vulnerable to collusion and extortion. I focus on one such informal monitor – the fair authorities at the trade fairs at Champagne – asking why the fairs survived for centuries instead of instantly crumbling in the face of the authorities’ overwhelming incentives to collude. Milgrom et al.’s (1990) seminal model of the Champagne fairs is not equipped to deal with collusion, though it does deal with extortion. I show that there is a collusion-proof equilibrium in an alternative model with a competing fair and merchant guilds/self-governed merchant communities and show how these institutions interact with the Champagne fair authorities’ incentives. This is invulnerable to collusion, extortion and “reverse extortion” (unscrupulous clients threatening to smear a monitor's reputation unless bribed). I highlight the crucial roles of competition among monitors, the existence of a collective body to organize coordinated punishment of monitors caught colluding, and network effects among the monitor's customers that exacerbate any punishment.